Reliability and construct validity of the SF-36 in Turkish cancer patients - (:unkn) unknown (SPRINGER, 2005)
In this study, we assessed the reliability and construct validity of the SF-36, Turkish version on 419 cancer patients. Cronbach's alpha coefficients surpassed the 0.70 criterions for all subscales indicating good internal consistency. Results of the test-retest method showed that the stability coefficients for the eight subscales of the SF-36 ranged between 0.81 and 0.94. Principal components factor analysis with varimax rotation confirmed the presence of seven factors in the SF-36: physical functioning, role limitations due to physical and emotional problems, mental health, general health perception, bodily pain, social functioning, and vitality. In conclusion, the Turkish version of the SF-36 is a suitable instrument that could be employed in cancer research in Turkey.
Keywords: cancer patients; construct validity; reliability; SF-36